2018
DOI: 10.1021/acscatal.7b04201
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen/Deuterium (H/D) Exchange Catalysis in Alkanes

Abstract: The catalytic exchange of hydrogen and deuterium (H/D exchange) in light alkanes has been studied for almost a century. While alkanes and their C−H bonds are relatively inert, H/D exchange studies have shown that a large number of materials can catalytically activate these bonds. These studies helped elucidate the mechanisms by which alkane C−H bonds interact with catalytic materials. This Review serves to highlight this area of research, focusing on two main classes of heterogeneous materials, metals and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 228 publications
0
61
0
2
Order By: Relevance
“…-CH 2 ·). A second possibility is di-adsorption, which includes αα, αβ and αγ types (Sattler, 2018). Bond (2006) suggests that αβ is the favored exchange mechanism for small straight-chain alkanes.…”
Section: Position-specific Exchange Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…-CH 2 ·). A second possibility is di-adsorption, which includes αα, αβ and αγ types (Sattler, 2018). Bond (2006) suggests that αβ is the favored exchange mechanism for small straight-chain alkanes.…”
Section: Position-specific Exchange Mechanismsmentioning
confidence: 99%
“…Thus, this mechanism also predicts faster central exchange and slower terminal exchange. A third possibility is ionic exchange, which is involves the dissociation of either proton or hydride (Schimmelmann et al, 2006;Sattler, 2018). Alexander et al (1984) reported that alkyl H exchange happens exclusively on the position adjacent to the position that is more stable for carbocation.…”
Section: Position-specific Exchange Mechanismsmentioning
confidence: 99%
“…Это обычный многоступенчатый синтез с использованием дейтерированных реагентов или дейтерирование родительского соединения методом Н/D изотопного обмена [5]. Изотопный протий-дейтериевый обмен (H/D) зависит от рН и природы катализатора [3,15].…”
Section: отличие дейтерия от протия с позиции фармацевтической химииunclassified
“…It is, therefore, anticipated that advances in material science or inorganic catalysis will also enrich the armory of HIE reaction methods in the future. For readers interested in the HIE reactions at alkane C–H bonds in hydrocarbons, we like to direct you to the recent review of Sattler …”
Section: Aliphatic C(sp3)‐h Hydrogen Isotope Exchange Reactionsmentioning
confidence: 99%